The thermal conductivity of polyamorphous state of solid monohydroxyl alcohols - Krivchikov, A.I.; Korolyuk, O.A.; Sharapova, I.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
New measurement results on the thermal conductivity of solid ethyl alcohol С2Н5ОН in the interval from 2 Kto the melting temperature are presented. The annealing effect in the thermal conductivity of the orientationally ordered phase of the alcohol has been observed in a wide range of temperatures. This phase was obtained as a result of the irreversible first-order phase transition from an orientationally disordered crystal of cubic structure at T = 109 K. The thermal conductivity was observed to increase as the monoclinic lattice changed from a less stable phase to a more stable one. The growth may be due to the improved quality of the completely ordered crystal. A comparative analysis of the temperature dependences of thermal conductivity κ(T) was performed for solid monohydroxyl alcohols CH3OH, С2Н5ОН, С2D5ОD, C3H7OH and C4H9OH in the disordered orientational and structural states. At low temperatures the thermal conductivity of a series of monohydroxyl structural glasses ofalcohols increases with the mass of the alcohol molecule by a linear dependence.